HUBUNGAN ANTARA PERLAKUAN ORANGTUA DENGAN MOTIVASI BELAJAR SISWA DISEKOLAH - Solina, Wira; Erlamsyah, Erlamsyah; Syahniar, Syahniar (Konselor, 2013)
Parentsmust provide appropriate treatment of child development, so that children can perceive parenting provided, for motivate learning. Actually many students have not motivated to learn because of parenting. The research purpose to reveal correlation the parenting with student learning motivation. Research methods used are descriptive correlational. Result of research show parenting is quite good, student motivationis quite high andthere is asignificant correlation parenting with student motivation.